The Geography of Art IX International Scientific Conference / IX Международная научная конференция «География искусства» - LAVRENOVA OLGA A. / ЛАВРЕНОВА О.А. (Наука телевидения, 2023)
Geography of Art is an interdisciplinary synthesis inspired by the theme of creative genius comprehending and exploring space. The project began in 1994, with the first collection of works published at the Russian Heritage Institute under Yuri Vedenin’s guidance; the first conference was held in 2009. In recent years, the conferences have been held annually under the auspices of the Institute of Scientific Information on Social Sciences of the Russian Academy of Sciences, the Russian Academy of Arts, GITR Film and Television School, the Russian State University for the Humanities. The IX International Conference Geography of Art of 2023 united culturologists and art historians, geographers and philosophers from all over Russia and abroad. Traditionally, the participants discussed issues related to artistic space of literary and pictorial works, local texts, geographical and cartographic images, and virtual spaces created by art. As always, a separate section was devoted to “mastering,” using, modeling space in screen and photography art. An innovation in the scholarly dispute of the 2023 conference was the culturological and anthropological discourse on the visual image genesis and transformation from archaic to modern times, as well as the transgression of genius loci in the online media and virtual space.